Delayed elimination of high‐dose methotrexate and use of carboxypeptidase G2 in pediatric patients during treatment for acute lymphoblastic leukemia. Issue 7 (14th December 2016) - Svahn, Thommy; Mellgren, Karin; Harila‐Saari, Arja; Åsberg, Ann; Kanerva, Jukka; Jónsson, Ólafur; Vaitkeviciene, Goda; Stamm Mikkelssen, Torben; Schmiegelow, Kjeld; Heldrup, Jesper
Abstract: Background: Carboxypeptidase G2 (CPDG2 ) can be used as rescue treatment in cases of delayed methotrexate elimination (DME) and Mtx‐induced nephrotoxicity. Procedure: Between July 2008 and December 2014, all children (1.0–17.9 years) in the Nordic countries diagnosed with Philadelphia chromosome negative acute lymphoblastic leukemia (ALL) were treated according to the Nordic Organization for Pediatric Hematology and Oncology (NOPHO) ALL 2008 protocol, including administration of six to eight high‐dose (5 g/m 2 /24 hr) Mtx (HDMtx) courses. The protocol includes recommendations for CPDG2 administration in cases of DME (clinicaltrials.gov NCT01305655). Results: Forty‐seven of the 1, 286 children (3.6%) received CPDG2 during 50 HDMtx courses at a median dose of 50 IU/kg. In 49% of the cases, CPDG2 was used during the first HDMtx course. Within a median of 6 hr from CPDG2 administration, the Mtx concentration decreased by 75% when measured with immune‐based methods, and by 100% when measured with high‐performance liquid chromatography. The median time from the start of Mtx infusion to plasma levels ≤ 0.2 μM was 228 hr (range: 48–438). The maximum increase in plasma creatinine was 375% (range: 100–1, 310). Creatinine peaked after a median of 48 hr (range: 36–86). Mtx elimination time was shorter in patients with body surface area < 1 m 2 (median 198.5 vs. 257 hr; P = 0.004) and was inversely correlated to the maximum creatinine increase (209 vs. 258 hr; P = 0.034). All patients normalized their renal function as measured with s‐creatinine. Conclusions: CPDG2 administration is highly effective as rescue in case of delayed Mtx clearance. Subsequent HDMtx courses could be administered without events in most of the patients.